1978
DOI: 10.1021/ma60065a026
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Resonance Study of the Segmental Motion and Local Conformations of Poly(L-glutamic acid) in Aqueous Solutions

Abstract: The segmental motions and the local conformations of poly(L-glutamic acid) in aqueous solutions have been investigated by magnetic resonance spectroscopy as a function of pH or pD and temperature. The ESR of spin-labeled PLGA with a nitroxide group attached to the end of the main chain or of a side chain indicates a sharp decrease of the mobility of this group at the random coil -* «-helix transition. The analysis of the 250 MHz !H NMR spectra at different temperatures and pD shows the prevalence of the gauche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…It is important to note that the signal of a-proton in PLGA block clearly appeared at 4.2 ppm (see Fig. 1c), which indicates that PLGA blocks take a coil chain conformation and remain solvated in aqueous media [50]. Zeta potential measurements were used to further confirm the corona structures of the micelles.…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that the signal of a-proton in PLGA block clearly appeared at 4.2 ppm (see Fig. 1c), which indicates that PLGA blocks take a coil chain conformation and remain solvated in aqueous media [50]. Zeta potential measurements were used to further confirm the corona structures of the micelles.…”
Section: Resultsmentioning
confidence: 98%
“…and a single peak centered at ca 2.1 p.p.m. are assigned to -CH 2 protons and -CH 2 protons, respectively, of PNaGA in the random-coiled state (Markley et al, 1967;Tsutsumi et al, 1978). The three peaks in the A spectra are assigned to CH 2 protons of PNaGA in the helical state, but the assignment of each peak was not made here.…”
Section: And 1 H Nmr Measurementmentioning
confidence: 99%
“…It was found that case (1) with a = 89 explains fairly well the spin-lattice relaxation time of fl-carbon as shown in figure 7. The complete results will be published elsewhere [21].…”
Section: Discussionmentioning
confidence: 99%